PENINGKATAN KUALITAS PRODUK OLAHAN SUSU DENGAN PENYIMPANAN HASIL PRODUKSI YANG EFEKTIF - Nurul Asfiah; Sandra Irawati; Yulist Rima Fiandari (Studi Kasus Inovasi Ekonomi, 2021)
The service was carried out to one of the SME groups in the tourist village of Café Sawah Pujon. The method used is the method of observation and active participation. The findings of the obstacles that were found were the unavailability of tools that accommodate processed products in a large capacity and the quality of processed milk that needed to be improved. This service is very much needed by 'Aisyiyah's SME group, to improve the quality of dairy products, which have become a mainstay for this group. The training was carried out by developing flavor variants of pasteurized milk, yogurt, and ice cream with better taste quality. The training that is carried out provides increased abilities for participants. Another activity carried out at this service is to assist with tools that can accommodate large amounts of dairy products within a certain period. Various activities are carried out aimed at increasing production capacity by maintaining consistency of quality. The dimensions of quality that are durability, conformance to specifications, features , reliabilty , aesthetics also perceived quality.